2010
DOI: 10.1029/2009gl042193
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of the precipitation dipole transition zone in the western United States

Abstract: El Niño‐Southern Oscillation‐related hydroclimatic variability in the western United States is characterized by a north–south dipole pattern of precipitation anomalies with opposing signs. Here I use a high‐resolution dataset to analyze spatiotemporal patterns in the transition zone between the centers of opposite association. Results indicate that the transition zone is spatially limited west of the continental divide, consisting of a narrow zone within the 40–42°N latitude band and portions of eastern Washin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
192
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(211 citation statements)
references
References 22 publications
(29 reference statements)
19
192
0
Order By: Relevance
“…On the other hand, other researchers (Zhang et al, 1996; have considered the PDO to be independent of ENSO, but that reinforcing interactions could occur between the two oscillations. Gershunov and Barnett (1998), and Wise (2010) found that there occurred an enhanced response of the Pacific-North American mode (Wallace and Gutzler, 1981) when the PDO and ENSO were in the same phase, i.e. when the PDO was in a negative phase and a La Niña occurred, the Pacific Northwest experienced cooler and wetter conditions, and the American southwest and northern Mexico experienced even warmer and drier conditions than normal in a negative PDO alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other researchers (Zhang et al, 1996; have considered the PDO to be independent of ENSO, but that reinforcing interactions could occur between the two oscillations. Gershunov and Barnett (1998), and Wise (2010) found that there occurred an enhanced response of the Pacific-North American mode (Wallace and Gutzler, 1981) when the PDO and ENSO were in the same phase, i.e. when the PDO was in a negative phase and a La Niña occurred, the Pacific Northwest experienced cooler and wetter conditions, and the American southwest and northern Mexico experienced even warmer and drier conditions than normal in a negative PDO alone.…”
Section: Discussionmentioning
confidence: 99%
“…Jacques et al, 2010;Whitfield et al, 2010;Wise, 2010). Winter precipitation in this region is higher (lower) and winter temperatures are cooler (warmer) when the PDO is in a negative (positive) phase, and vice versa in southwestern North America (Mantua et al, 1997;Mantua and Hare, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…However, various modes of ENSO are associated with different impacts on western NA hydroclimate (Ashok et al, 2007), and teleconnections can vary on decadal-to-centennial time scales (Gershunov and Barnett, 1998b), suggesting that southwest hydroclimate does not always respond to ENSO variability in a linear manner based on our modern understanding of southwest hydroclimate and ENSO correlations (Heyer et al, 2017). However, despite teleconnection variability (Gershunov and Barnett, 1998b), dipole variability (Wise, 2010) and different modes of ENSO (Ashok et al, 2007), paleo-sedimentary records suggest teleconnections between ENSO and southwest climate are similar to those observed in the modern record, and have persisted at century-millennial time scales (Barron and Anderson, 2010;Antinao and McDonald, 2013;Kirby et al, 2014;Hart et al, 2015). Further, paleoecological records have revealed the ENSO phenomenon is correlated with fire regimes of the southwest (Swetnam and .…”
Section: Regional Descriptionmentioning
confidence: 99%
“…Strong El Niño years in the modern record typically result in higher-thannormal winter precipitation in the southwestern United States; while strong La Niña typically causes lower-than-normal winter precipitation and is typically associated with regional drought (Shinker and Bartlein, 2009). Studies have identified a northto-south precipitation dipole correlated with ENSO in the western U.S., showing a strong relationship in the southwest between cool season (Oct-Mar) precipitation and El Niño events (Dettinger et al, 1998;Wise, 2010). Further, many studies have shown statistically significant correlations between ENSO and western North America precipitation, specifically in the southwest where spatially coherent correlations are found during the cool season (Dettinger et al, 1998;Heyer et al, 2017).…”
Section: Regional Descriptionmentioning
confidence: 99%
See 1 more Smart Citation